Cadmium telluride (CdTe) thin-film photovoltaics: A sustainable energy solution to support national energy resilience - Annisa Mutiara Putri Abdul; Adhi Kusumadjati; Gustav Irgi Aldhiantoro; Dinda Rahma Dewi; Moh. Hisni Alfan Baarik; Cornelia Victoria Anghel (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
Cadmium Telluride (CdTe) is one of the most promising materials in thin-film solar cell technology; however, its application faces challenges related to efficiency limitations and environmental risks. This study aims to evaluate the performance characteristics, environmental impact, and sustainability potential of CdTe in Solar Power Plant, known in Indonesia as Pembangkit Listrik Tenaga Surya (PLTS) applications. A systematic literature review was conducted, analyzing more than 40 scientific articles and industrial reports published over the last 15 years, covering efficiency, material availability, recycling strategies, and lifecycle assessments. The results indicate that commercial CdTe modules achieve efficiencies between 7–10%, while laboratory devices exceed 22%. CdTe demonstrates superior performance under high temperatures and low-light conditions, but concerns remain regarding cadmium toxicity and the limited availability of tellurium. The study concludes that CdTe holds significant potential as a cost-effective and efficient solar technology, provided that robust recycling systems and responsible material sourcing practices are implemented.